'Close, not close': Migrant artists negotiating transnational mother-daughter intimacies. (May 2019) - Winarnita, Monika; Dirgantoro, Wulan; Wilding, Raelene
Abstract: The feminisation of migration is contributing to growing awareness of the transformation of familial subjectivities and emotional terrains as a result of transnational movements. The emotional lives and identities of women have often been at the forefront of these investigations. However, the female roles investigated are largely limited to those of mothers and domestic workers. In this paper, we explore how another gendered identity has also been transformed by international migration: that of the daughter. We avoid repeating analyses of the gendered experiences of domestic workers by drawing on an analysis of research conducted with young female artists who are first or second-generation migrants. Reflecting on research interviews and examples of their work exploring mother-daughter relationships, we consider how independently mobile young women navigate the emotional and geographic distances in their intimate relationships with their mothers, both within and beyond their artistic works. We argue that the navigation of 'close, not close' relationships with their mothers shapes their gendered subjectivities by informing the social and cultural identities they enact across the distances of generations on the one hand, and of nations, on the other. Highlights: Investigates emotional reflexivity as part of the mother-daughter relationship and of 'dutiful daughterhood'. Explores the experiences and practices of young female migrant artists from Indonesia and the Philippines. Challenges definitions of women migrating from the Philippines and Indonesia as foreign domestic workers. Considers mother-daughter intimacy as reflected and expressed artistically. Challenges notions of intimacy and distance in intergenerational relations.